n método para la identificación de tres especies crípticas de Protesilaus, (Lepidoptera: Papilionidae) del sur de Brasil, basado en su morfología genital - Ricardo Murillo Hiller, Luis (2007)
I describe the male genital structures of three species of but-terflies from Rio Grande do Sul, Brazil. Their external patterns do not differ enough to determine one species from another. All inhabit the same areas at the same time of the year. In an attempt to find a constant difference among them, as well as to establish the range of variability in each species, series of butterflies from different localities were dissected. The diagnostic structures found in all three species were named and drawn for their identification. Color patterns, width, separateness and presence or absence of the black bands and the color of the frons are not useful for recognizing P. nigricornis from P. stenodesmus or P. helios. The species group studied shows major morphological variability. For that reason, species level identification can be extremely difficult, particularly if the specimens are deteriorated. In conclusion, the only reliable way to correctly identify this spe-cies is by dissection of male genitalia.